Analysis of Liability and Legal Protection of Land Deed Officials (PPAT) Review of Court Decision No. 43/Pdt.G/2017/PN. Slt - Fajar Fitrio Dwi Nugroho (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
This research aims to explore the legal protections and responsibilities assumed by Land Deed Officials (PPATs), particularly in the context of Court Decision No. 43/Pdt.G/2017/PN. Slt. Using a case study approach, we identify factors that affect the legal responsibilities of PPATs under the judgment. While evaluating whether the existing legal system has provided adequate protection to them. This research uses a juridical sociological approach method with a descriptive analytical nature, as well as primary data collection techniques through interviews and secondary data through an inventory of books, documents, and articles. The results of the analysis show that Court Decision No. 43/Pdt.G/2017/PN. Slt provides an important insight into the responsibility of PPAT in making land deeds. The implications of these findings are discussed in the context of improving a more effective legal system to ensure adequate protection for PPATs and the public interest in property transactions. The results show that PPATs must be responsible for the validity of the deeds they make in accordance with the rules and principles, and they are responsible for attending the trial. However, based on the precautionary principle, PPATs need to increase caution in making land payment settlement notes. In relation to the legal protection of PPATs, they are entitled to both mental and physical protection from interference and threats from any party.